59‐1: Liquid Crystal Technology for Solving Key Optical Challenges in Virtual and Augmented Realities. Issue 1 (29th May 2019) - Lu, Lu; Peng, Fenglin; Wang, Mengfei; McEldowney, Scott; Silverstein, Barry
Abstract : Augmented reality (AR) and virtual reality (VR) smart glasses require breakthroughs in displays and optics. In the liquid crystal field, recent progress shows promising results for solving key optical challenges in AR/VR near to eye displays, such as vergence‐accommodation conflict, high resolution foveated display, occlusion, and compact optical combiners. Combining liquid crystal technology with conventional optical tools could enable truly comfortable AR/VR head mounted displays that meet size, weight, and efficiency specs.